Inhibition of iNOS Induction and NF-kappa B Activation by Taste Compounds from the Edible Mushroom Tricholoma caligatum (Viv.) Ricken - Erol, EBRU; EROL, EBRU; Ali, Zulfiqar; Ozturk, Mehmet; Khan, Shabana; Khan, Ikhlas A. (My University, 2020)
Tricholoma caligatum (Viv.) Ricken is an edible mushroom that belongs to matsutake group. The first chemical investigation of the three different extracts of Tricholoma caligatum resulted in two new compounds, 8-demethoxylascivol (1) and 8-epi-lascivol (2) and six known compounds, lascivol (3), trametenolic acid (4), ergosterol (5), ergosterol peroxide (6), 5 alpha, 6 alpha-epoxyergosterol (7), and cerebroside B (8). Their structures were elucidated by spectroscopic analyses including 1D and 2D NMR data. The biological activities of all the compounds were evaluated toward multiple targets related to inflammation and metabolic disorder such as NF-kappa B, iNOS and ROS. The findings of this study reveal that the edible mushroom Tricholoma caligatum could be a potential source for anti-inflammatory bioactive metabolites.